Synthesis and Spectral Properties of 1-Substituted Phenyl-3-(p-methoxycarbonyl)phenyl-5-phenylformazans - Senoz, Hulya; Yildirim, Ebru; Tezcan, Habibe (Asian Journal of Chemistry, 2013)
Formazans 1-14 were prepared by the coupling reaction of phenylhydrazones and diazonium salts of aniline or -NO2, -CH3, -OCH3, -I, substituted anilines. The phenylhydrazones were synthesized by condensation of benzaldehyde or methyl-4-formylbenzoate with phenylhydrazine. The structures of the compounds were confirmed by IR, 1H NMR and 13C NMR. The dependence of lmax upon the type of substituents and their positions on the phenyl ring was investigated using UV-visible spectra.